Resistencia y renovación: la subversión mítica en Adiós, Ayacucho de Julio Ortega - Rivera Rodríguez, Kevin (Pontificia Universidad Católica del Perú, 2024)
The essay proposes that in Julio Ortega's novel Adiós, Ayacucho, a confrontation with hegemonic-Western rationality takes place from an alternative rationality that comes from the Andean worldview. The analysis is based on decolonial theory to explain the presence of this other way of thinking, through the incarnation of the protagonist, Alfonso Cánepa, in two mythical-religious figures: the Andean condemned man and the Inkarrí. It also makes use of Mijaíl Bajtín conceptualization of carnival to delve into the processes of inversion, restitution and renewal present.

El ensayo propone que en la novela Adiós, Ayacucho de Julio Ortega se produce una confrontación con la racionalidad hegemónico-occidental desde una racionalidad alternativa que proviene de la cosmovisión andina. El análisis toma como base la teoría decolonial para explicar así la presencia de esta otra forma de pensamiento, mediante la encarnación del protagonista, Alfonso Cánepa, en dos figuras mítico-religiosas: el condenado andino y el Inkarrí. También se hace uso de la conceptualización del carnaval de Mijaíl Bajtín para ahondar en los procesos de inversión, restitución y renovación presentes.
Resistance and renewal: mythical subversion in Adiós, Ayacucho of Julio Ortega
Keywords: Condemned; Inkarri; Renovation; Incarnation; Myth; Condenado; Inkarrí; Renovación; Encarnación; Mito; https://purl.org/pe-repo/ocde/ford#6.02.05